Current Situation of Classroom Management at Primary Schools to Meet the Requirements of the 2018 General Education Curriculum in Vietnam (Journal of Contemporary Educational Policies and Practices, 2022)
The 2018 General Education Curriculum in Vietnam is a competence-based program in which students actively learn under teacher’s guidance. Also, learning activities are very diverse, which requires teachers to manage their classrooms effectively. The study employed questionnaires to collect data from 226 parents and 336 teachers in public and private schools in Vietnam. The research focuses on three main aspects of classroom management (CM) in response to the implementation of the 2018 general education curriculum: Creating classroom environments; Establishing classroom rules; Student behavior management. The research results showed that the participating teachers and parents appreciated the surveyed activities in classroom management. Creating environments and establishing rules form the basis for student behavior standards. Therefore, both the teachers and parents quite agreed to promote these two activities for primary students. However, the parent’s support was lower than the teacher’s, especially in managing student behavior. In order to manage the school, it is essential to involve all stakeholders, including a close relationship between teachers and parents.
Keywords: Classroom environment; classroom rules; student behavior management; classroom management